2007
DOI: 10.1088/0022-3727/40/23/001
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of metastable, epitaxial PrCo7films with high energy density

Abstract: Two series of epitaxial Pr–Co thin films with a nominal composition of Pr2Co17 were grown on Cr buffered MgO(1 1 0) single crystal substrates by pulsed laser deposition, in which the deposition temperature TD and the post annealing temperature Tann were varied. Pr–Co films prepared at different deposition temperatures crystallize in the metastable PrCo7 structure (TbCu7 type) for 450 °C ≤ TD ≤ 650 °C. For TD ≤ 600 °C these films exhibit a (h 0 0) texture, with the c-axis of the Pr–Co grain aligned in the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…2(b)], the Pr 1−x Hf x Co 5+ı alloys maintain the uniaxial magnetocrystalline anisotropy with the [0 0 1] easy magnetization direction throughout the whole homogeneity range (this observation agrees with the earlier studies [12,17]). Data presented in Fig.…”
Section: Magnetic Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…2(b)], the Pr 1−x Hf x Co 5+ı alloys maintain the uniaxial magnetocrystalline anisotropy with the [0 0 1] easy magnetization direction throughout the whole homogeneity range (this observation agrees with the earlier studies [12,17]). Data presented in Fig.…”
Section: Magnetic Propertiessupporting
confidence: 89%
“…doi:10.1016/j.jallcom.2010.11.090 may indeed substantially increase the Curie temperature and saturation magnetization [and, therefore, the theoretical maximum energy product (BH) max ] of the uniaxially anisotropic PrCo 5 compound. Patra et al [17] recently reported epitaxial Pr-Co thin films with the TbCu 7 -type structure and a (BH) max of 43 MGOe, which is 30% higher than (BH) max of the best Sm-Co magnets. Unfortunately, epitaxial stabilization of the PrCo 5+ı structure is not possible in bulk magnets.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PrCo 5 exhibits a spin reorientation ͑SR͒ transition from an easy axis anisotropy along the crystallographic c-axis ͑which persists above the transition temperature͒ to an easy cone anisotropy around 107 K. 3 In our earlier report, 4 we revealed that epitaxial Pr-Co films ͑Ϸ80 nm͒ can be prepared on Cr buffered MgO͑110͒ substrates in a wide composition range with a single orientation of the c-axis which lies in the film plane along the MgO͓001͔ substrate edge. In that series, Pr-Co films crystallize in different phases like the PrCo 7 structure 5,6 and the PrCo 5 and Pr 2 Co 7 phases, which exist in a certain composition range. These highly textured epitaxial Pr-Co films exhibit excellent intrinsic and extrinsic magnetic properties.…”
Section: Introductionmentioning
confidence: 99%